Accounting Practices and Guiding Principles Influencing Shared Value Creation - Wadesango, Ongayi (International Journal of Economics and Financial Issues, 2023)
This study explored the shared value and the types. Porter and Kramer’s shared-value model is analysed; its critiques are outlined, and other approaches along with their weaknesses suggested by previous researchers, are explored. A documentary research approach, which consists of reviewing, analysing and examining information was adopted. The sources included journal articles, books, frameworks and guidelines. The results of the study indicated/revealed that value is not only accounted for in financial terms but also in intangible drivers, value creation processes result in predetermined output and outcomes which cannot be predetermined. The study also indicated that shared- value is a term that is not distinctively and commonly used as its components were not clearly spelt out. Researchers/ scholars have failed to distinguish it from other similar models of social and environmental responsibility. The study concludes that creating shared value from social and relations capital contributes towards increased productivity and sustainability of a company.